2018
DOI: 10.54386/jam.v20i1.505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meteorological parameters on incidence of brown leaf spot in rice crop under different planting methods

Abstract: The field experiments were conducted during three kharif seasons 2012, 2013 and 2014 to study the effect of meteorological parameters on brown leaf spot of rice under different transplanting dates, methods and plant population. The experiment was laid out in split-split plot design with two transplanting dates (15th June and 30th June) in main plots, three methods of planting (conventional, SRI and furrow) in sub plots and two plant population (625 and 300 plants per m2) in sub-sub plots with three replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In general, weather conditions that prevailed during the months of August, September and October were most favorable for the development of brown leaf spot disease. Multiple regression models were fitted for the prediction of disease severity under the given set of environmental circumstances because simple correlation did not show any significant relation between meteorological variables and disease progression.Similar results were observed by Dhaliwal et al (2018) who reported that relative humidity (morning) was positively correlated with brown spot severity. On the contrary, the temperature and disease severity was found negatively correlated with development of brown spot of rice.…”
Section: Discussionsupporting
confidence: 90%
“…In general, weather conditions that prevailed during the months of August, September and October were most favorable for the development of brown leaf spot disease. Multiple regression models were fitted for the prediction of disease severity under the given set of environmental circumstances because simple correlation did not show any significant relation between meteorological variables and disease progression.Similar results were observed by Dhaliwal et al (2018) who reported that relative humidity (morning) was positively correlated with brown spot severity. On the contrary, the temperature and disease severity was found negatively correlated with development of brown spot of rice.…”
Section: Discussionsupporting
confidence: 90%
“…The fungicides Mancozeb and Zineb recommended earlier have been found insufficient for management of the brown spot disease. The favourable environmental conditions like temperature, relative humidity and rainfall during the rice season aggravate the severity of brown spot disease (Dhaliwal, 2018) [4] . Effective management of brown spot disease may be achieved by using resistant cultivars, fungicides, biological agent and cultural practices.…”
Section: Introductionmentioning
confidence: 99%